Polymer Capsules as a Theranostic Tool for a Universal In Vitro Screening Assay—The Case of Lysosomal Storage Diseases. (1st October 2015) - Nazarenus, Moritz; Abasolo, Ibane; García‐Aranda, Natalia; Voccoli, Vladimir; Rejman, Joanna; Cecchini, Marco; Schwartz, Simó; Rivera_Gil, Pilar; Parak, Wolfgang J.
Abstract : Lysosomal storage disorders are rare genetic diseases characterized by a lysosomal enzyme deficiency. The defect leads to an accumulation of normally degraded substrates within the lysosomes. The accumulation of polymeric capsules inside the lysosomes is exploited to create a universal in vitro theranostic tool for lysosomal storage disorders. The diagnostic ability of this tool based on pH‐sensitive fluorophores is demonstrated by monitoring the lysosomal pH in Krabbe‐disease cell models upon accumulation of the substrate psychosine. Krabbe‐affected cells maintain their normal pH, while the lysosomes of their healthy counterparts undergo alkalinization, which can be correlated to toxicity. The potential of this tool for therapy based on enzymes inside the capsules is evaluated within the context of enzyme replacement therapy. Enzymatic degradation of the capsules inside the lysosome leads to release of the encapsulated active enzyme and the prevention of adverse effects of accumulated psychosine upon capsule‐based delivery of the functional enzyme is confirmed. In Fabry‐affected cells the intracellular enzymatic activity of the drug Replagal released from capsules shows the same kinetics as the free enzyme, which constitutes the current therapy, although the activity is smaller. Encapsulating Replagal nevertheless represents an alternative to receptor‐mediated endocytosis, overcoming limitations such as low or absent receptor expression. Abstract : Polymer multilayer capsules for pH‐sensing and enzyme delivery are prepared, and the intracellular application is demonstrated for two different models of lysosomal storage disorders. Nondegradable sensor capsules represent the diagnostic tool for monitoring the accumulation of cytotoxic psychosine in the cells, while biodegradable enzyme‐filled capsules deliver the remedy to the lysosomes of the cells.